Risk Factors Of Dental Career Events In Pres School Children Ra Al-Hakim Village Damage Subscription Kesamben Blitar District - Nur Mei Lila, Rahma; Sodik, Muhammad Ali (Universitas STRADA Indonesia, 2019)
Oral health is important for general health and quality of life. Dental health is important, especially for child development. Dental caries is a dental health disorder. The purpose of this study was to identify risk factors for dental caries in preschool children in RA-ALHAKIM kindergarten Siraman village, Kesamben district, Blitar district. The design of this study is quantitative with a cross sectional approach. The population of this study were students of Ra Al-Hakim Tk A and Tk B. The sample size of 67 respondents was taken using Simple Random Sampling technique. Dependent variable Occurrence of dental caries in children, independent variables of knowledge, role of parents, and behavior of children. The results of the analysis using logistic regression with a value of α 0.05. The results showed that there was no significant effect between children's knowledge of the occurrence of dental caries in children with p-value of 0.258, there was a significant influence between the role of parents on the occurrence of dental caries in children with p-value of 0.048, there was a very significant influence between children's behavior on the occurrence of dental caries in children with a p-value of 0,000, the most influential factor with the occurrence of dental caries in children with a p-value of 0,000 is the variable of child behavior In order to reduce the incidence of dental caries in children it is necessary to have an active role from parents, or the school principals, teachers, and the entire school community in carrying out their role in providing actions not only to provide knowledge, but also concrete actions for dental caries in children can be reduced